Bottom up fabrication of (9, 0) zigzag and (6, 6) armchair carbon nanotube end-caps on the Rh(1 1 1) surface. (April 2015) - Abdurakhmanova, Nasiba; Mueller, A.; Stepanow, S.; Rauschenbach, S.; Jansen, M.; Kern, K.; Amsharov, K. Yu
Abstract: The exploration and wide application of single walled carbon nanotubes (SWCNTs) require the development of new synthetic approaches enabling facile and fully rational CNT fabrication. In this communication the conversion of two precursors yielding the potential CNT seeds of (9, 0) zigzag and (6, 6) armchair nanotubes using surface-assisted cyclodehydrogenation on the Rh(1 1 1) single-crystal surface is reported. The conversion efficiency found is nearly 100% and the CNT-caps remain thermally stable on the Rh surface up to 820 K which is high enough for subsequent SWCNT growth. It is shown that Rh is a suitable catalyst for the controllable synthesis of SWCNTs by the surface assisted bottom-up strategy.